Citrus Fruit Pectins: Isolation, Amidation, Characterization and Adsorbing Capacity of lead ions (Research, Society and Development, 2022)
Metals in effluents cause problems for humans and nature, so looking for substances to adsorb them is extremely important. The literature reports the relevance of pectins as heavy metal biosorbents. Thus, the objective was to extract, modify and compare pectins from Sicilian lemon and Bahia orange, aiming at the use and recovery of these residues, for Pb2+ adsorption. Extraction was performed with ammonium oxalate and characterizations by infrared, hydrogen nuclear magnetic resonance, gel permeation chromatography and high-performance liquid chromatography. The materials were evaluated in terms of kinetic models and adsorption capacity as a function of pH and concentrations. The modification was confirmed by FT-IR from the bands corresponding to the amides. The spectra showed that both are of low degree of esterification, with 36.86% and 33.33% for lemon and orange, respectively. However, they presented high percentages of amidation with 61.00% and 50.00% for lemon and orange, respectively. Both were classified as polymolecular, polydisperse and among the identified sugars, only rhamnose was not detected in orange pectin. The samples showed excellent removal rates, 94.86% for orange and 86.45% for lemon, at a concentration of 250 mg/L, adapting to the pseudo-second order model. Therefore, amidated pectins are important for Pb2+ chemisorption, due to their high adsorbent capacity at various concentrations, highlighting the orange that showed increasing percentages of removal at all concentrations.